Encounters in quest of Christian womanhood : the Basel Mission in pre- and early colonial Ghana - Sill, Ulrike. (Studies in Christian Mission, 2010)
Christianity has come to be a religion embraced especially by women and not least in Africa. This book provides one of the as yet rare case studies for the early stages of this development: how African women on the pre- and early colonial Gold Coast (Ghana) encountered Basel Mission Christianity, 1843-1885. Popular interpretations have tended to describe Christianity as either 'empowering' or 'domesticating' African women. Looking at variegated push-and-pull factors and in its focus on the agency of Ghanaian women this detailed analysis moves beyond. It situates the quest for Christian womanhood as part of trans-national discourses and exchanges, as well as local interactions, and writes a social history that is at once transnational and transcultural.